Dampak Pengembangan Sarana Pariwisata Terhadap Peningkatan Jumlah Pengunjung Di Wisata Alam Air Panas Angseri, Tabanan - I Gusti Ayu Widyarini; I Nyoman Sunarta (JURNAL DESTINASI PARIWISATA, 2018)
tourism facilities then the interest of visitors to travel will increase. Angseri nature hot water is located in Tabanan District, while in the field of existing tourism facilities are considered good enough, although there are still some facilities that have not received attention from the manager such as waiting queue and park for children. This type of research is qualilative and quantitative research, the research method used in this research method of interview, observation, and documentation, the techniques of determining informants used are snowball procedures, and data analysis using qualitative descriptive analysis. The results obtained in this study is that tourism facilities available in the field can be good enough, although there are still some facilities that have not met the standards, when the development of tourism facilities conducted by the Angseri hot water tourism management proved to have a good influence on the increasing number of visitors who each month increased Keywords: Development Impact, Tourism Facility, Number of Visitors